Cross-cultural validation of a short form of the Oral Health Impact Profile for temporomandibular disorders - Segu` M, Collesano V, Lobbia S, Rezzani C. (Blackwell Synergy, 2005)
We set out to develop and validate an Italian version of the Oral Health Impact Profile Questionnaire (OHIP) that is appropriate for use in temporomandibular disorders (TMD).